Se substituted 2D-gC3N4 modified disposable screen-printed carbon electrode substrate: A bifunctional nano-catalyst for electrochemical and absorption study of hazardous fungicide. (September 2022) - Nataraj, Nandini; Chen, Tse-Wei; Akilarasan, Muthumariappan; Chen, Shen Ming; Al-Ghamdi, Abdullah Ahmed; Elshikh, Mohamed S.
Abstract: The indispensable usage of pesticides for the control and prevention of pests is probable and includes several types based on the problems in the crops. Among them, fungicides, are one problem-solving agent curing fungal developments. the disproportionate use of fungicides will lead to environmental deterioration and several health issues. The assessment of such fungicides is highly motivated to be detected. Under the class of two-dimensional materials, graphitic carbon nitride (GCN) with high surface area and high electrocatalytic activity was chosen as electrode material. The efficiency of GCN was improved with the subsequent substitution of selenium (Se) into the triazine ring as Se-GCN. The structural and surface analysis was done and the layered structure was proved. The electrochemical detection of CBM showed a lower detection limit at 6 nM with a linear range 0.099 μM–346.9 μM while, the absorption studies showed a LOD of 20 nM with a linear range of 0.099 μM–182.09 μM. The orange juice and vegetable extract samples had good recovery with CBM at Se-GCN modified disposable screen-printed electrode. The developed disposable electrode was more sensitive with 6.45 μAμM −1 cm 2 sensitivity and highly reactive with CBM. Moreover, the developed sensor will be more effective in sensing applications to avoid the menace generated by several agents. Graphical abstract: Image 1 Highlights: Non-metal substitution of selenium with graphitic carbon nitride was exhibited. The electrochemical sensing of carbendazim with Se-GCN/SPCE was exposed with a linear range of 0.099 μM–346.9 μM. The absorption of carbendazim (CBM) was studied with a linear range of 0.099 μM–182.09 μM. Both the electrochemical and UV analysis showed a limit of detection about 6 nM and 20 nM. The dual functional Se-GCN nanocomposite was highly capable of sensing CBM in fruits and vegetable real samples.